Interpreting Visuality in the Middle Ages: The Iconographic Paradigm of the Refectory of the Monastery of San Salvador de Oña - Ana Maria Cuesta Sánchez (Religions)
The research area of the interaction between religion, politics, and medieval Hispanic art has been pioneering and at the cutting edge of contemporary historiography in recent years. The deployment of iconographic and calligraphic motifs in medieval religious spaces has been identified as a key means of propagating legitimating messages of power and disseminating Christian doctrines. This interdisciplinary study proposes an analysis of the artistic vestiges present in the refectory of the Monastery of San Salvador de Oña (Burgos), with a view to establishing their decorative evolution during the 14th century and their symbolic significance. In order to establish a chronological proposal for the remains, the historical, artistic, and architectural contexts of the monastery are analyzed. This is complemented by a study of materials and techniques and a symbolic and iconographic analysis of the signs of power and evangelical concepts from the time of Pedro I until the transition to the Trastámara dynasty. In this way, a cross-disciplinary investigation is proposed, with the aim of elucidating how a sacred artistic work situated within a secular context can serve multiple purposes of political and religious legitimation through the adaptation of its iconography over time.